2016
DOI: 10.1073/pnas.1609769113
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic antenna−reactor complexes for photocatalysis

Abstract: Metallic nanoparticles with strong optically resonant properties behave as nanoscale optical antennas, and have recently shown extraordinary promise as light-driven catalysts. Traditionally, however, heterogeneous catalysis has relied upon weakly light-absorbing metals such as Pd, Pt, Ru, or Rh to lower the activation energy for chemical reactions. Here we show that coupling a plasmonic nanoantenna directly to catalytic nanoparticles enables the light-induced generation of hot carriers within the catalyst nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
569
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 436 publications
(578 citation statements)
references
References 43 publications
7
569
0
2
Order By: Relevance
“…[38][39][40][41] Recently it has been shown that Pd nanoparticle-decorated, oxide-coated Al nanocrystals enable efficient plasmon-induced photocatalysis at the Pd surface, where the plasmonic and catalytic functions were effectively distinct. 42 This general structure has been called an "antenna-reactor" complex, where the plasmonic nanoparticle is the antenna and the catalytic particle, which can be interchanged based on desired reactivity, is the reactor. In an antenna-reactor complex, the local field induced by the photoexcited antenna particle drives a "forced" plasmon in the nonplasmonic, catalytic nanoparticle: this forced plasmon can serve as a direct source of hot carriers in the catalytic particle to drive chemical processes without the need for charge transfer between 5 the antenna and the reactor components of the nanocomplex.…”
Section: 33mentioning
confidence: 99%
“…[38][39][40][41] Recently it has been shown that Pd nanoparticle-decorated, oxide-coated Al nanocrystals enable efficient plasmon-induced photocatalysis at the Pd surface, where the plasmonic and catalytic functions were effectively distinct. 42 This general structure has been called an "antenna-reactor" complex, where the plasmonic nanoparticle is the antenna and the catalytic particle, which can be interchanged based on desired reactivity, is the reactor. In an antenna-reactor complex, the local field induced by the photoexcited antenna particle drives a "forced" plasmon in the nonplasmonic, catalytic nanoparticle: this forced plasmon can serve as a direct source of hot carriers in the catalytic particle to drive chemical processes without the need for charge transfer between 5 the antenna and the reactor components of the nanocomplex.…”
Section: 33mentioning
confidence: 99%
“…This antenna-reactor complex allows absorption enhancements in poorly light-absorbing catalytic metals [35]. The feasibility of these heterostructures has been demonstrated using Al as "antenna" and Pd as "reactor" heterodimers [35] and decorated spherical nanoparticles [36]. Aluminum-cuprous oxide antenna-reactor nanoparticles have also been proven to be an efficient photocatalytic heterostructure [37].…”
Section: Aluminummentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In particular, heterogeneous photocatalysis that couples light with chemical reactions is of paramount importance in chemistry and energy applications. [8][9][10][11][12][13][14][15][16] Plasmonic enhancement is currently a hot topic in catalysis-driven chemistry and photonic materials due to its important role as the main mediator bridging solar energy with other energy forms. For instance, the photocatalytic water splitting reaction used for biomimetic plant photosynthesis represents a promising solution to the growing demands for clean and sustainable energy.…”
Section: Introductionmentioning
confidence: 99%